2018
DOI: 10.1371/journal.pone.0191353
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin prevents acetaminophen-induced hepatotoxicity in mice

Abstract: Acetaminophen or paracetamol (APAP) overdose is a common cause of liver injury. Silymarin (SLM) is a hepatoprotective agent widely used for treating liver injury of different origin. In order to evaluate the possible beneficial effects of SLM, Balb/c mice were pretreated with SLM (100 mg/kg b.wt. per os) once daily for three days. Two hours after the last SLM dose, the mice were administered APAP (300 mg/kg b.wt. i.p.) and killed 6 (T6), 12 (T12) and 24 (T24) hours later. SLM-treated mice exhibited a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 57 publications
(57 reference statements)
10
53
0
Order By: Relevance
“…TR extract and silymarin showed similar resistance to toxicity induced by acetaminophen which indicates that the valuable compounds present in TR extract possess similar properties as shown by silymarin. The present study is in accordance with Papackova et al (), which support PS group results. They showed that induced hepatotoxicity injury can be reduced by silymarin.…”
Section: Discussionsupporting
confidence: 94%
“…TR extract and silymarin showed similar resistance to toxicity induced by acetaminophen which indicates that the valuable compounds present in TR extract possess similar properties as shown by silymarin. The present study is in accordance with Papackova et al (), which support PS group results. They showed that induced hepatotoxicity injury can be reduced by silymarin.…”
Section: Discussionsupporting
confidence: 94%
“…In such case, reactive oxygen species, nitric oxide, peroxinitrite derivatives, lipid peroxidation and protein nitrates have roles in hepatotoxicity (24). Several studies demonstrated that paracetamol mediated oxidative damage and hepatotoxicity in rats and mice, resulting in enhancement of the liver parameters (25)(26)(27). In the present study oral administration of a single dose of 2 g paracetamol/kg body wt on the 22nd day induced oxidative stress and toxicity in the liver.…”
Section: Discussionsupporting
confidence: 46%
“…Silybin interferes in oxidative stress, accumulation of fat in liver, and insulin resistance (Federico, Dallio, & Loguercio, ; Marin et al, ). It improves functional liver tests (Aller et al, ) and leads to a reduction in hepatotoxicity induced by high doses of acetaminophen and can diminish oxidative stress in mice (Brandon‐Warner et al, ; Papackova et al, ). In patients with chronic hepatitis C, silymarin has antiviral (Lani et al, ; Polyak, Ferenci, & Pawlotsky, ) and hepatoprotective role (Polyak et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…and leads to a reduction in hepatotoxicity induced by high doses of acetaminophen and can diminish oxidative stress in mice (Brandon-Warner et al, 2012;Papackova et al, 2018). In patients with chronic hepatitis C, silymarin has antiviral (Lani et al, 2015;Polyak, Ferenci, & Pawlotsky, 2013) and hepatoprotective role (Polyak et al, 2013).…”
mentioning
confidence: 99%